Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Sympodial bamboo species differ in carbon bio-sequestration and stocks within phytoliths of leaf litters and living leaves - Tingting Xiang; Yuqi Ying; Jiangnan Teng; Zhangting Huang; Jiasen Wu; Cifu Meng; Peikun Jiang; Caixian Tang; Jianmin Li; Rong Zheng (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids - Mingjun Cheng; Mingmin Zheng; Shipeng Yang; Yang Li; Xingchun Dong; Jing Li; Rulong Sun; Huaxiong Li; Shufeng Zhou; Yuanqi Wu; Tingzhao Rong; Qilin Tang (Euphytica, 2016)
Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by reciprocal crosses of maize and Zea perennis . By using dual-color genomic in situ hybridization, intra- and intergenomic meiosis pairing of these polyploids were quantified and compared with regard to its genome organization and cytoplasm background. In the four neoallopolyploids, the stability of maize genome is consistently lower than that of Z. perennis genome. Additional, the stability of maize genome is affected by genome ploidy. The cytoplasm, genome composition and their interaction do have the special role in chromosome paring and the meiosis behaviors in Zea allopolyploids vary significantly and showed non-diploidization. Z. perennis cytoplasm may give a relatively relaxed environment for maize genome.